Challenges and appropriate policy portfolios for (almost) mature renewable electricity technologies. Issue 1 (March 2017) - Held, Anne; Boßmann, Tobias; Ragwitz, Mario; del Río, Pablo; Janeiro, Luis; Förster, Sonja
This paper assesses challenges arising for renewable energy technologies that have achieved a certain maturity level in terms of technology development, costs and market penetration. We identify these challenges, which diverge from challenges for less mature technologies and, based on three case studies, we analyse how some of the challenges have materialised and have been dealt with in practice. Case studies include experiences with the occurrence of negative prices in Germany, the question of how to deal with a market situation characterised by overcapacity in Spain and the problem of social opposition towards the construction of renewable power plants in the UK. Finally, we suggest solutions to deal with these issues in order to ensure the 2030 target is achieved, taking into account the changing framework conditions.